2002
DOI: 10.5713/ajas.2002.61
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Feeding Systems on Carcass and Non-Carcass Parameters of Black Bengal Goat

Abstract: The experiment was conducted to find out the effect of four feeding systems namely; stall feeding, tethering, restricted grazing and grazing on carcass characteristics of Black Bengal goat. Twenty four does of approximately 1 year of age were randomly selected for four treatments of feeding systems having 6 replications in each. Stall fed goats were kept into house all time and adequate amount of natural grass were supplied for ad libitum feeding. Goats of tethering group were tethered for eating natural grass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 4 publications
3
17
4
Order By: Relevance
“…The dressing percentage was gradually increased due to gradual increase of concentrate supplementation (Table 3). The dressing percentage of present study was higher than the value for Black Bengal goat and cross bred (41.48% to 43.73%) observed by Abedin et al (2005), Moniruzzaman et al (2002) and Das et al (2005). However, a lower dressing percent and age of Black Bengal goats (38.61%) was also reported by Singh et al (1986) in Indian Black Bengal goat.…”
Section: Carcass Characteristicscontrasting
confidence: 49%
“…The dressing percentage was gradually increased due to gradual increase of concentrate supplementation (Table 3). The dressing percentage of present study was higher than the value for Black Bengal goat and cross bred (41.48% to 43.73%) observed by Abedin et al (2005), Moniruzzaman et al (2002) and Das et al (2005). However, a lower dressing percent and age of Black Bengal goats (38.61%) was also reported by Singh et al (1986) in Indian Black Bengal goat.…”
Section: Carcass Characteristicscontrasting
confidence: 49%
“…Spleen of the present study was almost similar but shank was differed to Sultana et al (2010), where they showed that shank % was 1.2, 1.8 and 2.2 at 6, 9 and 12 months of age, respectively. Moniruzzaman et al (2002) stated that slaughter age had a significant effect on dressing percentage and meat quality.…”
Section: Effect Of Different Slaughter Ages On Carcass Traits Of Jamu...mentioning
confidence: 99%
“…It is commaon practice among smallholder farmers under the crop-livestock farming systems to tether or herd goats [ 1 ]. The grazing systems are mainly done to prevent goats from damaging crops or grain in storage.…”
Section: Introductionmentioning
confidence: 99%